Genetic Structure of Liriomyza trifolii (Diptera: Agromyzidae) Associated With Host Plants From Southeastern Mexico. Issue 1 (31st December 2018) - Pérez-Alquicira, Jessica; van der Knaap, Esther; Mercer, Kristin; McHale, Leah; Mitchell, Thomas; Luna-Ruiz, Jose; Texocotitla-Vázquez, Esther; Vargas-Ponce, Ofelia; Michel, Andy
Abstract: Host-associated differentiation (HAD) has played a major role in insect diversification at both macroevolutionary and microevolutionary scales. This evolutionary process has been reported in insects associated with wild and domesticated plant species. In particular, domesticated species harbor large genetic and phenotypic diversity associated with traits of human interest, including variation in nutrition, phenology, fruit, and leaf shape. This diversity may alter selection regimes affecting insect evolution and host specialization. The genus Liriomyza includes highly polyphagous species that are characterized for living and feeding inside plant leaves. Ecological and genetic data suggest the presence of cryptic species within this genus. Moreover, there is evidence of HAD in a group of populations of Liriomyza trifolii (Burgess) associated with Capsicum annum L. (Solanaceae). In this work, we explored HAD in L. trifolii populations from southeastern Mexico, and inquire into differentiation specific to peppers based on cytochrome oxidase I. We also evaluated the relationship between the genetic structure of leafminers and the different types of C. annuum . Our main results did not support previous findings of specialization of L. trifolli on C. annuum . Nevertheless, we found a divergent group of haplotypes associated to Allium cepa (Aspargales: Amaryllidaceae) in sympatric condition to Physalis philadelphica Lam. (Solanales: Solanaceae) and C. annum, suggesting the presence of HAD, as well as significant genetic differentiation of L. trifolii associated to peppers from Oaxaca and Yucatán.